2003
DOI: 10.3998/ark.5550190.0004.a27
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-ethyl-2-methyl-3-arylindanes. Stereochemistry of five-membered ring formation

Abstract: A natural dimer of asarone and several analogues were obtained by acid-catalysed cyclodimerisation of styrenes and by formal [3+2] cycloaddition. A study of the influence of the aromatic ring substitution pattern on the stereochemistry of the reactions was carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Thus, regio- and diastereoselective trapping of the allylic cation 22 by in situ generated indene 9z to give an intermediate tertiary carbocation 23 , followed by intramolecular cyclization to the cation 24 , and selective elimination would provide the 21 . The formation of 21 is an example of a formal [2π + 2π] cycloaddition . The remarkable selectivity exhibited in the formation of 21 can be rationalized, in part, by attack of indene 9z from the less hindered face onto the more electron-deficient position of the allylic cation 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, regio- and diastereoselective trapping of the allylic cation 22 by in situ generated indene 9z to give an intermediate tertiary carbocation 23 , followed by intramolecular cyclization to the cation 24 , and selective elimination would provide the 21 . The formation of 21 is an example of a formal [2π + 2π] cycloaddition . The remarkable selectivity exhibited in the formation of 21 can be rationalized, in part, by attack of indene 9z from the less hindered face onto the more electron-deficient position of the allylic cation 22 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the benzyl alcohols 1-(3,4-dimethoxyphenyl)propanol ( 11) and 1-(3,4-methylendioxyphenyl)propanol (12) react with styrenes 4-methoxystyrene (13) and 2,4,5-trimethoxystyrene (15) to render two pairs of stereoisomeric indanes 14a, 14b and 16a, 16b, respectively, with identical stereoselectivity to that obtained with SnCl 4 [22] but in a shorter time and with higher yield.…”
Section: Formal [3 + 2] Cycloaddition Reactionsmentioning
confidence: 99%
“…In previous papers, numerous examples of this type of reaction using SnCl 4 as catalyst were published [21,22]. Here, the results obtained using MPA/S as catalyst and the better reaction conditions for each pair of reactants are presented (Table 3).…”
Section: Formal [3 + 2] Cycloaddition Reactionsmentioning
confidence: 99%
“…Secaloside A (Figure ), found in pollen extract, was responsible for antitumor activity . Synthetic approaches to prepare the arylindanes from benzyl alcohols and benzhydrols with styrene derivatives have also been investigated under acidic conditions. ,, In these reactions, although the phenyl ring substituents were shown to significantly affect the yield and diastereoselectivity, a convincing explanation has not been provided as yet.…”
Section: Introductionmentioning
confidence: 99%
“…2:1) were characterized. 20 Although this type of reaction is known to proceed as a formal [3 + 2] cycloaddition reaction, 14 it is suggested that the methoxy and hydroxy groups attached to the phenyl ring play an important role in the reactivity and stereoselectivity.…”
Section: ■ Introductionmentioning
confidence: 99%